Modelling for fabrication of microelectrodes by localized electrochemical deposition for micro-electrodischarge machining - Habib, Md Ahsan; Saleh, Tanveer; Rahman, Mustafizur Azizur (SAGE Publications Inc., 2010)
This paper presents the theoretical modelling and experimental investigation on the effect of different localized electrochemical deposition (LECD) parameters for fabricating a variety of microstructures. In order to estimate the rate of the deposition and the condition of the deposited structure, a set of mathematical relations is developed with the help of Faraday’s laws of electrolysis and the Butler–Volmer equation. Mathematical simulation results are validated by experimental results. In this experimental process copper was deposited on the cathode surface. The variation in structure of the deposited electrode is achieved by changing the shape of a nonconductive mask. Thismaskis fabricated by an on-machine micromilling processandit is kept in contact with the cathode surface. The whole system is immersed in an acidified copper sulphate plating solution. This study gives a clear indication of the optimized operating range for theLECD process in order to fabricate high aspect ratio microstructures. Futhermore, the performance of the LECD electrode is evaluated by the fabrication of microholes on high-melting-point material such as a stainless steel workpiece.